2017
DOI: 10.2196/mhealth.7040
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Patient Engagement Applications During Pregnancy: A Qualitative Assessment of the Patient’s Perspective

Abstract: BackgroundWith growing demand for medical information and health applications in pregnancy, the potential of electronic health (eHealth) and mobile health (mHealth) solutions in clinical care is increasingly unfolding. However, we still do not know how pregnant women engage with mobile apps, how such apps impact routine medical care, and whether benefit expectations are met. Whereas recent research has raised the subject of user distribution and analyzed the content of pregnancy applications, there is still a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 38 publications
8
93
0
6
Order By: Relevance
“…Hundreds of smartphone apps are available to provide advice and information about pregnancy and parenting. Studies have found that pregnant women and mothers in the global North are beginning to use apps in significant numbers [10][11][12][13]. Many of these provide functions that encourage women to monitor and survey their own bodies and those of their children, thereby entering very personal details.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of smartphone apps are available to provide advice and information about pregnancy and parenting. Studies have found that pregnant women and mothers in the global North are beginning to use apps in significant numbers [10][11][12][13]. Many of these provide functions that encourage women to monitor and survey their own bodies and those of their children, thereby entering very personal details.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that health professionals guide women in their use of mhealth tools during pregnancy [18] and that professionally endorsed apps be used adjunctively by health professionals as part of their maternity health care protocol [55]. Further, to ensure the accessibility and uptake of reliable app-based pregnancy information, the provision of free hospital-endorsed apps with complementary resources, such as supportive training and education to use them [12], are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…One US study found Google searches were the most common mode of information seeking, particularly early in pregnancy [16]. An important factor for many women was the ability to obtain information instantly and easily [6,15,17,18]. Importantly, in one global study almost half of the 613 women surveyed reported that their online information-seeking was triggered by dissatisfaction with health professionals regarding both the information provided and insufficient time to ask questions.…”
Section: The General Populationmentioning
confidence: 99%
See 2 more Smart Citations